Integrasi Senyawa Alam Dan Teknologi Komputasi Dalam Pengembangan Obat Modern: Tinjauan Kimia Medisinal - Amin, Saeful; Chahyani, Shahila Nor; Ariyanti, Ira Akhira; ma'aruf, Muhammad alliful (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The rapid evolution of modern medicinal chemistry has increasingly transcended traditional trial-and-error methodologies, embracing a more integrative paradigm that combines the exploration of bioactive natural compounds with advanced computational technologies. This study aims to critically examine the significance of such integration in contemporary drug development by analyzing 15 scientific publications, comprising 10 peer-reviewed international journals and 5 scholarly works by Saeful Amin. Employing a descriptive-qualitative literature review approach, this research synthesizes current findings to identify emerging trends, methodological advancements, and their implications for pharmaceutical innovation. The results reveal that natural compounds including flavonoids, alkaloids, and terpenoids exhibit remarkable potential as lead compounds due to their extensive structural diversity, evolutionary optimization, and broad-spectrum biological activities. Concurrently, computational techniques such as molecular docking, quantitative structure–activity relationship (QSAR) modeling, and artificial intelligence (AI)-driven drug design significantly enhance the efficiency, precision, and predictive capacity of drug discovery processes. Moreover, the synergistic integration of in silico simulations with in vitro experimental validation is shown to be pivotal in accelerating lead identification, optimizing pharmacokinetic properties, and reducing the risk of late-stage drug failure. In conclusion, the convergence of natural product research and computational methodologies represents a transformative strategy in modern medicinal chemistry, enabling the development of more effective, targeted, and sustainable therapeutic agents while addressing the growing complexity and cost of pharmaceutical research.